“Saudagar Bandoeng”, 1906—1930-an - Dede Rohayati (Lembaran Sejarah, 2018)
The growth of Bandung as a city at the beginning of the 20th century, has produced urban groups that dominate parts of the urban economy. One group was known as Saudagar Bandoeng or the Bandung indigenous Muslim merchants. They started growing as middle-class urban Muslims who rely on their economic life in the commercial sector. There are three reasons for the emergence of Saudagar Bandoeng, namely the rejuvenation of Pasar Baru market in 1906, the rise of batik trading and the modernization of Bandung facilitated the traffic goods and people to and from the city of Bandung. The Saudagar Bandoeng emerged as a community of santri traders which were relatively different from that of rural santri traders. The birth of the Soedara Association (Himpoenan Soedara) as an organization for santri traders to promote indigenous economic sector in Bandung represented one of the rise of merchant nationalist identity as has been seen in other cities such as Surakarta.